Physicochemical Marker for Determination of Value-Adding Component in Over-Ripe Thai Mango Peels - Pirawan Chaiwan; Pornchai Rachtanapun; Yuthana Phimolsiripol; Warintorn Ruksiriwanich; Chunmei Li; Lu Luo; Dan Shen; Hsiao-Hang Chung; David George; Tibet Tangpao; Sarana Rose Sommano; Piyachat Sunanta (Horticulturae)
Thailand is a prominent global producer of mangoes, providing a wide range of mango cultivars and dealing with the challenge of managing biomass. Thus, biorefining mango peel to extract valuable components has the potential to reduce organic waste and create a new revenue source for the mango processing sector. This study aims to examine the physiology, physiochemical, and chemical characteristics in peel of nine Thai mango cultivars, along with the relationship between their characteristics. The Thai mango cultivars Mahachanok, Chok anan, and Rad exhibited a yellow appearance, while the other six cultivars appeared yellow-green. However, the firmness of the fruit was directly correlated with the firmness of the pulp. A proximate composition study revealed that the predominant constituent of mango peel was carbohydrates, comprising up to 75% of its composition. This was followed by fibre, which accounted for up to 13%. The Nga mango had the highest levels of total phenolic content (220 mgGAE/g) and total flavonoid content (5.5 mgCE/g). The primary phenolic acids identified in Thai mango peel were epicatechin, caffeic acid, catechin, and gallic acid. The Mahachanok cultivar exhibited the highest antioxidant activity, as determined by the ABTS and DPPH assays, with values of 85.67% and 85.78%, respectively. This study demonstrated the connections between the physiochemical characteristics of mangoes and their chemical compositions in different cultivars, indicating the possibility of choosing particular cultivars for extracting targeted bioactive compounds. The multivariate analyses revealed that there was no correlation between the physiochemical and chemical profiles of mangoes. This study highlights the significance of mango peel as a valuable by-product that has significant environmental and economic ramifications for the mango processing industry.